An Ex Vivo Evaluation of Cenobamate Administered via Enteral Tubes - Ferrari, Louis (Drugs R D, 2020)
BACKGROUND: Cenobamate is a new, Food and Drug Administration (FDA)-approved oral antiepileptic drug for treatment of focal seizures in adults. This study examined recovery of cenobamate from suspensions administered through ex vivo enteral feeding tubes. METHODS: Suspensions containing 100 and 200 mg of cenobamate were prepared (five duplicates for each dose), passed through five vertically standing tubes, and collected into flasks. The flasks containing the suspensions were rinsed with deionized water, and this content was also injected into the tubes and collected in the flasks. Acetonitrile, isopropyl alcohol, and trifluoroacetic acid were added to the flasks, followed by deionized water to a concentration of 500 (100-mg cenobamate) and 400 (200-mg cenobamate) µg/mL. A 3-mL aliquot from each suspension was placed into a 10-mL flask, diluted to volume, and mixed, resulting in final concentrations of 150 and 120 µg/mL, respectively. All suspensions were analyzed by high-performance liquid chromatography (LC). The % LC recovery of cenobamate was calculated for each suspension, and mean % LC for duplicates. RESULTS: The % LC recovery of cenobamate from the 100-mg suspensions ranged from 96.2 to 99.1%, with mean % LC recovery between 96.3 and 98.3%. The % LC recovery of cenobamate from the 200-mg suspensions ranged from 97.1 to 102.6%, with mean % LC recovery between 98.5 and 101.7%. CONCLUSION: The mean % LC recovery of cenobamate was within the predetermined acceptable range of 90.0–110.0%, suggesting no adhesion or adsorption of cenobamate to enteral feeding tubes. Delivery of cenobamate suspension via enteral feeding tubes may be a viable route of administration for patients who cannot swallow tablets.